PHYSICOCHEMICAL ASPECTS OF MAGNETITE GABBRO FORMATION IN THE LAYERED INTRUSION OF THE WESTERN PANSKY TUNDRA, KOLA PENINSULA, RUSSIA - Latypov R.M.; Chistyakova S.Yu. (My University, 2001)
Magnetite gabbro occurs in the central part of the layered intrusion of the western Pansky Tundra as layers and lenticular bodies from 20 to 100 m thick and from hundreds of meters to 10 km long. They show fine-grained textures and contain cumulus magnetite, iron-rich pyroxenes, and low-calcium plagioclase. The transition from the enclosing gabbronorite (Pl-Cpx-Opx cumulate) through gabbronorite with inverted pigeonite (Pl-Cpx-Opx-Pig# cumulate) to the magnetite gabbro bodies with inverted pigeonite (Pl-Cpx-Opx-Pig#-Mgt cumulate) is accompanied by successive appearance of new cumulus phases, pigeonite and magnetite (phase layering); gradual increase of clinopyroxene fraction on the expense of orthopyroxene (modal layering); regular increase in the iron content of pyroxene; and decrease in the anorthite content of plagioclase (cryptic layering). These observations allow us to interpret the magnetite gabbro with inverted pigeonite as the final product of the Fenner trend of chamber differentiation of the initial melt of the Western Pansky Tundra intrusion. It is assumed that during intrusion consolidation, the residual melt portions were concentrated in isolated subchambers elongated in accord with the general structural plan of the massif. The opposing walls of the subchambers converged gradually during crystallization, and fluid pressure increased continuously, while the composition of liquid changed and its volume decreased. Tectonic movements and (or) high fluid pressure resulted in wall fracturing and fluid loss from the subchambers. This brought the melt into a state of strong oversaturation and caused its rapid crystallization and formation of fine-grained magnetite gabbro depleted in incompatible elements, which were removed from the system by the fluid phase.